Description and characteristics of 81 patients attending the Reference Center for Multiple Sclerosis of the coastal region of the state of São Paulo - Brazil Descrição e características dos 81 pacientes em seguimento no Centro de Referência em Esclerose Múltipla do litoral paulista - Yara Dadalti Fragoso; Ana Patricia Perez Fiore (Arquivos de Neuro-Psiquiatria)
OBJETIVE: to register multiple sclerosis (MS) patients residing in the coastal region of the State of São Paulo (CEREM Litoral Paulista). METHOD: Individual interviews with identified cases of MS. RESULTS: 81 individuals with diagnosis of MS agreed to come for registration (62 females [76.5%], 19 males [23.5%]). 65% of all patients were residents of the city of Santos. The mean age of these patients was 43 years (14 to 74 years), and the Expanded Disability Status Scale (EDSS) was < 5.5 in 76.5% of the cases. 82.7% of the assessed patients presented the relapsing/remitting form of MS. 81.5% of all patients were undergoing treatment with immunomodulators. CONCLUSION: Due to their clinical profile, patients seem to come to CEREM Litoral Paulista for prescription of immunomodulators. There is a clear need to identify other cases in the region and to allow other forms of treatment to be put into practice. OBJETIVO: Registrar os pacientes portadores de esclerose múltipla (EM) residentes na região do litoral paulista (CEREM Litoral Paulista). MÉTODO: Entrevistas individuais com casos identificados de EM. RESULTADOS: 81 indivíduos com diagnóstico de EM (62 mulheres [76,5%] e 19 homens [23,5%]) concordaram em comparecer para registro no centro. 65% do grupo total de pacientes eram residentes da cidade de Santos. A idade média destes pacientes era 43 anos (14 a 74 anos), e o Expanded Disability Status Scale (EDSS) foi < 5,5 em 76,5% dos casos. 82,7% dos pacientes registrados apresentava a forma remitente-recorrente de EM. 81,5% de todos os pacientes estava recebendo tratamento com imunomoduladores. CONCLUSÃO: Pelo perfil clínico, os pacientes parecem vir ao CEREM Litoral Paulista para prescrição de imunomoduladores. Existe uma clara necessidade de identificar outros casos na região e permitir que outras formas de tratamento sejam implantadas.